Challenges and Solutions for Keeping Maternity and Gynecology Services Functioning Comprehensively in Secondary Level Health Care Facility in COVID-19 Pandemic Situation Using a Clinical Approach - Jayanta Kumar Biswas; Pratistha Lall; Soumen Das Poddar; Vikas Srivastava; Ajith Nilakantan (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: With the nationwide lockdown in India, and with a near-exclusive focus on the novel coronavirus disease (COVID-19) there has been a great deal of neglect in the management of other illnesses leading to significant mortality and morbidity. We aimed to assess the feasibility of keeping obstetrics & gynecology services in a secondary care hospital functioning (in terms of regional experiences and comprehensive patient care measures) in the COVID-19 pandemic situation using a clinical approach.